Ferritin‐Hijacking Nanoparticles Spatiotemporally Directing Endogenous Ferroptosis for Synergistic Anticancer Therapy. Issue 51 (14th November 2022) - Zhu, Luwen; You, Yuchan; Zhu, Minxia; Song, Yanling; Zhang, Jucong; Hu, Jiahao; Xu, Xinyi; Xu, Xiaoling; Du, Yongzhong; Ji, Jiansong
Abstract: Existing ferroptosis as an iron‐dependent form of regulated cell death primarily relies on importing exogenous iron. However, the excessive employment of toxic materials may cause potential adverse effects on human health. Herein, a ferritin‐hijacking nanoparticle (Ce6‐PEG‐HKN15 ) is fabricated, by conjugating the ferritin‐homing peptide HKN15 with the photosensitizer chlorin e6 (Ce6) for endogenous ferroptosis without introducing Fenton‐reactive metals. Once internalized, the designed Ce6‐PEG‐HKN15 NPs can specifically accumulate around ferritin. With laser irradiation, the activated Ce6 in nanoparticles potently generates reactive oxygen species (ROS) surrounding ferritin. Abundant ROS not only helps to destroy the iron storage protein and activate endogenous ferroptosis but also directly kill tumor cells. In turn, the released iron partially interacts with intracellular excess H2 O2 to produce O2, thereby enhancing photodynamic therapy and further amplifying oxidative stress. Overall, this work highlights the possibility of endogenous ferroptosis via spatiotemporally destroying ferritin, offering a paradigm for synergistic ferroptosis–photodynamic antitumor therapy. Abstract : A ferritin‐hijacking nanoparticle (Ce6‐PEG‐HKN15 ) is fabricated by conjugating the ferritin‐homing peptide HKN15 with the photosensitizer chlorin e6 (Ce6), which can induce ferroptosis through activation of endogenous iron. This strategy highlights the possibility of endogenous ferroptosis via spatiotemporally destroying ferritin, offering a paradigm for synergistic ferroptosis–photodynamic antitumor therapy.